FACTORS RELATING TO WORK STRESS IN PRODUCTION OF UNIT WORKERS IN PT. INDO SURYA KENCANA (International Journal of Psychosocial Rehabilitation, 2020)
Job stress occurs when work demands exceed someone's ability to handle or control work. Based on the results of preliminary studies, workers of PT. Indo Surya Kencana shows that 17 out of 20 workers (85%) experience job stress. This study aims to determine the factors associated with work stress on production unit workers at PT. Indo Surya Kencana in 2019. This study used a cross sectional design with a sample size of 73 respondents, the sampling technique used the Probability Sampling method with univariate and bivariate data analysis using the Chi-square test. The study was conducted in November 2019- January 2020. The highest proportion of univariate results was job stress (76.7%), workload (65.8%), work period ≥5 years (69.9%), shift work on evening and night (54.8%), workers who attended training (53.4%), workers of non-productive age (47.9%), unmarried workers (53.4%). There is a relationship between workload (PR = 2,396, 95% CI = 1,477-3,886), work period (PR = 1,582, 95% CI = 1,064-2,352), work shift (PR = 1,375, 95% CI = 1,036-1,825), training (PR = 1,529, 95% CI = 1,177-1,940), marriage status (PR = 1,347, 95% CI = 1,022-1,775) to work stress. It is hoped that the company will identify psychosocial hazards, conduct counseling and stretch once every 2 hours.